A rare case of perosomus etumbis in a tellicherry goat - KUMAR, S SATHESH; VEL, K SENTHIL; Kannan, T P; GAJENDRAN, K (The Indian Journal of Animal Reproduction, 2023)
A double-headed monster fetus was delivered by caesarian section in a pluriparous crossbred (Desi xHF) pregnant cow was presented with acute labor and dystocia. Fetus was fully developed female calf with twoheads joined by a single neck, two oral cavities, four eyes, two mandibles, two tongue, single esophagus, singlethorax and abdomen, vulva, two fore limbs and two hind limbs which can be classified as Dicephalus DipusDibrachious Monster.
Keywords: Monster perosomus elumbis; tellicherry goat; congenital anomaly